Título Padrão - Ogawa, Masayoshi; Price, Ralph L.; Barroso, Maria Ângela Tomaz; Beserra, Frederico José (Arquivos de Ciências do Mar, 2018)
The purpose of the present study was to determine the nature of the liver oil of several species of sharks caught off the coast of northeastern Brazil.